ESTABLISHMENT OF A SANITATION-RESISTANT YOUTH VILLAGE IN MENDALO LAUT, MUARO JAMBI DISTRICT - Erris Erris; Ahmad Dahlan; Ramly Tarigan; V.A Irmayanti Harahap (Yayasan Education and Social Center, 2022)
The community's way of managing waste still relies on collecting, transporting, and disposing of it to the final processing site and tends to burn waste. Most people view waste as useless leftovers. It makes community participation in waste management minimal. One of the efforts to overcome this problem is to carry out empowerment activities so that the community is willing and able to make changes in managing the waste it produces. It is known that the level of knowledge of the community, especially teenagers in Mendalo Laut Village, is known that there are still many who do not understand the benefits of sorting waste that comes from the source